Penile Prosthesis Surgery: Current Recommendations From the International Consultation on Sexual Medicine. Issue 4 (1st April 2016) - Levine, Laurence A.; Becher, Edgardo; Bella, Anthony; Brant, William; Kohler, Tobias; Martinez-Salamanca, Juan Ignacio; Trost, Landon; Morey, Allen
ABSTRACT: Introduction: Penile prosthesis implantation has emerged as a definitive treatment to restore sexual function to the motivated man with erectile dysfunction. Substantial improvements in the design of inflatable devices have been made since they first became available more than four decades ago. Aim: To review the history of the penile prosthesis, the indications, preoperative evaluation, and patient and partner satisfaction. The current approaches to addressing intra- and postoperative complications, provide an understanding of prosthesis infection, and placement of these devices will be reviewed. Methods: A committee of worldwide experts in this field was assembled during the 2015 International Consultation on Sexual Medicine (ICSM) and performed a systematic review of the peer-reviewed published medical literature pertaining to penile prosthesis. Particular attention was given to higher level trials when available. Recommendations are based upon the Oxford Criteria. Main Outcome Measures: Unfortunately there is limited level 1 and 2 evidence, and where expert opinion was utilized, the decision was unanimous within the committee with a goal of presenting a clinically relevant guideline pertaining to penile prostheses. Results: Penile prosthesis has undergone an evolution over the past 40 years resulting in a more effective and reliable treatment for advanced erectile dysfunction not responding to less invasive methods including oral treatment with PDE5 inhibitors, vacuum erection device, and intracorporal injection therapy. It should be considered an appropriate treatment option for the man who wishes to restore erectile function and who understands the potential risk of mechanical failure and infection, both of which are less common now as a result of improvements made in device design as well as surgical protocols adhered to in the operating room. Patients must be clearly informed of the risks associated with penile prosthesis including mechanical failure, infection, shortening of the penis, change in sensation and configuration of the penis, as well as injury to local structures. Intraoperative complications are unusual but do occur and can usually be addressed intraoperatively to allow placement of the device at the time of initial surgery. Postoperative complications may also be addressed when they occur but may require more advanced reconstructive surgical techniques. Men with Peyronie's disease, corporal fibrosis due to infection, trauma, prior prosthesis explantation, priapism, and men who have undergone construction of a neophallus may require additional advanced maneuvers to obtain optimum results with a penile prosthesis. Conclusion: Penile prosthesis remains as an important, viable, and effective treatment for male erectile dysfunction that does not respond to other less invasive approaches or when these approaches are contraindicated or not acceptable to the patient. These devices provide the patient with the ability to engage in penetrative sexual activity without interfering with urination, ejaculation, sensation, or orgasm. Although mechanical failure can occur, the current devices are more reliable as a result of design modifications. Infection remains the most dreaded complication but since the introduction of antibiotic and hydrophilic coatings, infection is less common. Overall, patient and partner satisfaction appear to be reasonably high when a penile prosthesis is used to restore erectile function.